Analysis of the Effect of Visual Merchandising, Store Atmosphere and Sales Promotion on Impulse Buying Behavior - Nurudin, Nurudin (Journal of Digital Marketing and Halal Industry, 2020)
Consumer behavior undergoes a very dynamic and significant development, which is caused by various factors. Consumer behavior is related to the factors behind the interest and decision to buy. This study aims to determine the effect of visual merchandising, store atmosphere, and sales promotion on impulse buying behavior. The method used in this research is quantitative. The sample used is supermarket consumers in Demak. The sampling technique used purposive sampling. The data analysis technique used multiple linear regression. The results showed that visual merchandising had a significant effect on impulsive buying behavior, store atmosphere has a considerable impact on impulsive buying behavior, and sales promotion significantly affected impulsive buying behavior. Therefore, in the future, if you want to optimize buyer interest, these three factors need to be considered.